Efficacy of medicinal herb Asparagus racemosus (shatavari) as an aphrodisiac feed additive for enhancing reproductive performance of female brood stock of freshwater carp fish, Cyprinus carpio Linn. - SINGH, RANJEET; ANSAL, MEERA D (The Indian Journal of Animal Sciences, 2024)
Efficacy of shatavari (Asparagus racemosus) root powder (SRP) as an aphrodisiac fish feed additive was evaluated by feeding female brood stock of freshwater carp, Cyprinus carpio (Linn.) with experimental feeds (for 120 days), supplemented with SRP @ 1% (SRP1), 2% (SRP2), 3% (SRP3) and 4% (SRP4). Feed without SRP served as control (SRP0) feed. SRP improved reproductive performance of fish significantly at 3 and 4% incorporation levels, but best results were obtained at 4% level (SRP4), resulting in improved gonadosomatic index (41.23%↑) and relative fecundity (45.00%↑); supported with an upregulated hormone profile, viz. estradiol (53.36%↑) and progesterone (130%↑). Although, no significant changes were observed in the egg size, but egg quality was significantly improved in terms of protein and lipid content, indicating higher feed and energy reserve for larval development. The immuno-modulatory effect of SRP was indicated by 2.12 times higher haemoglobin and 1.61 times higher haematocrit values, with enhanced immunity [serum total protein (42.21%↑), albumin (53.91%↑), globulin (32.92%↑) and total immunoglobulin (68.48%↑)]; antioxidant markers [lipid peroxidation (44.56%↓) and superoxide dismutase (80.43%↑)]; and positive metabolic changes in respect to liver function [serum glucose (16.91%↓), alanine aminotransferase (27.88%↓) and aspartate aminotransferase (15.82%↓)] and lipid profile [serum cholesterol (17.33%↓) and triglycerides (13.10%↓)] of the shatavari fed fish (SRP4). The results indicated that racemosus root powder can be incorporated in common carp brood stock feed @ 4% for boosting its reproductive potential, with a projected fry production enhancement of 45%.